Qualidade e conservação pós-colheita de melão Cantaloupe "Torreon" para exportação - Anselmo, Francisca Deuzenir Marques (2007)
It was evaluated useful life postharvest Cantaloupe melons, hybrid `Torreon', submitted to the application postharvest of 1-MCP at different concentrations (0, 300 and 600 ppb) and two periods of exposition to the gas (6 and 12 hours),harvested in two different stadiums of maturation (50 and 75% stalk abscission layer) kept in storage cooled during 21 days and 28 days, aiming at exportation. The fruits were harvested in farms at Mossoró, RN-Brazil, being analyzed in the Laboratories of Physiology and Technology Postharvest of the Embrapa Tropical Agroindústria and of Tropical Fruits of the Department of Food Technology of the Federal University of the Ceará, in Fortaleza-CE. For the monitoring of the quality of the fruits during storage, its physical characterization how much to the loss of accumulated mass and external and internal firmness beyond visual evaluation acceptance second scale was made notes; in this scale if external color attributes to relative notes á, firmness, incidence of podridões and general appearance. Physical chemical analysis were performed of total chlorophyll content, soluble sugars, reducing sugars, totals carotenoids, coloration of the pulp, total soluble solid content, totals acidity (AT) and pH. According to visual evaluation, the application of the 1-MCP delayed the loss of firmne ss and green coloration of the fruits, as well as the incidence of rottenness. The maintenance of the firmness was confirmed through analyzes physical in the device texturometer. Fruits dealt with 1-MCP had presented greater firmness of that the fruits have controlled and this result was more effective with the increase of the dosage.